Relationship between rain and groundwater in the hydrogeological sectors of the South Basin of Ciego de Ávila (2021)
Introduction— Groundwater constitutes the main source of water in the province of Ciego de Ávila, Cuba; especially in agriculture, which occupies the main economic line, however the overexploitation of aquifers in the southern basin of the province puts the sustainability of this important resource at risk, which is renewed through the natural recharge of rainfall. Objective— To determine the relationship between precipitation and groundwater levels in the hydrogeological sectors CA-II-2 and CA-II-3 of the Ciego de Ávila South Basin, which can constitute a way for the efficient use of water for irrigation purposes in this area of great agricultural importance. Methodology— In the development of the research, different methodologies were used: selection of the most representative rain gauges, calculation of effective precipitation, determination of accumulated monthly and annual rainfall; as well as the annual rainfall of the wet and dry periods, completion of rainfall series by the linear regression method, use of the HidroEsta 2 program to obtain the mean hiperanual rainfall and the historical mean levels, absolute minimum and maximum of all the selected wells. The mean rainfall of the area of the sectors was determined with the Isohyet method and the charts of hiperanual limnigrams were constructed using the BARHIS software. Results— The investigation showed that the average rainfall in the area is 1303.6 mm, higher than the historical average for the province. The water levels in the aquifer range between 0.84 m and 12.98 m; where 7.21 m is the absolute average value. The year 1988 had great variations in rainfall, levels and the exploitation of groundwater. This study suggests the need to take measures that contribute to the rational use of groundwater in this overexploited basin due to the intensive use of water resources in agricultural irrigation. Conclusions— The study carried out was able to verify that the average rainfall in the area is 1303.6 mm, higher than the historical average for the province. The water levels in the aquifer range between 0.84 m and 12.98 m, with absolute averages of 6.52 m and 7.21 m respectively. The year 1988 presented high variability in rainfall, underground levels and the exploitation of groundwater.